Outcomes for a clinically representative cohort of hearing-impaired adults using the Nucleus® CI532 cochlear implant - Hey, Matthias; Neben, Nicole; Stöver, Timo; Baumann, Uwe; Mewes, Alexander; Liebscher, Tim; Schüssler, Mark; Aschendorff, Antje; Wesarg, Thomas; Büchner, Andreas; Greenham, Paula; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Hearing performance data was collected from a large heterogeneous group of subjects implanted with the Cochlear™ Nucleus® CI532 with Slim Modiolar Electrode, for the purposes of postmarket clinical follow-up. Data was analysed for factors which may predict postoperative speech recognition scores. Methods: Data was collected retrospectively from five German clinics for 159 subjects from March 2017 to August 2018. Hearing thresholds and recognition scores for monosyllabic words in quiet and sentences in noise were measured preoperatively and at 3 and 6 months postoperatively. Results: There was a mean gain of 44% points (95% CI 39–49%) at 6 months in monosyllable scores in quiet for implanted ears. Preoperative hearing thresholds in implant ears increased systematically with decreasing age; however, younger subjects had better baseline monosyllable scores with hearing aids compared with older subjects. Baseline performance alone explained 14% of the variation in postoperative scores. Residual hearing was preserved on average to within 22 dB at 250 Hz and 30 dB at 500 Hz of preoperative levels. Conclusions: In a large and varied cohort of routinely treated hearing-impaired adults, speech recognition with the CI532 for German monosyllabic words in quiet at 6 months was equivalent to performance reported at one year or more in other published studies. Although younger subjects had poorer preoperative pure-tone thresholds, they had better preoperative word recognition scores compared with older subjects, and also had higher post implant scores. Further research is required to identify if this phenomenon is just applicable to German health system assessment and referral practices.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Congenital hearing loss; Data logging; Elderly; Hearing aids; Perimodiolar; Speech perception